A Bibliometric Review of Lightweight Aggregate Geopolymer Concrete - Tan S.Q.; Lim N.H.A.S.; Saleh A.T.; Wei K.E.L.; Samadi M.; Huseien G.F. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The increase in cement production has had a noteworthy impact on the emission of greenhouse gases. As a result, it is essential to develop geopolymer concrete innovations to mitigate the environmental consequences. However, conventional geopolymer concrete not only requires heavy machinery and an increase in the cross-sectional area of structural supports, but it also endangers the operating safety of workers. Therefore, in recent times, lightweight concrete has gained significant attention due to its many advantages and benefits to the structure and construction sectors. Thus, the aim of this study is to carry out a bibliometric analysis of the lightweight geopolymer concrete and assess its fundamental characteristics to determine the research gap in this area. This review paper will benefit researchers in identifying the ongoing trend in lightweight aggregate geopolymer concrete, identifying more areas for additional study. It will also act as a knowledge source for policymakers, journal editors, professionals, and research organizations. ? 2024 by the authors.